ALTERNATE SOLUTION OF INTER-SCHOOL GANG FIGHT (SOSIOLOGICAL LAW REVIEW) - Silviana, Arina (Universitas Tadulako, 2018)
This research aim at knowing and analyzing the way how to solve the inter school in Makassar and knowing and analyzing the factors resulting the inter-school gang fight in Makassar. This research of empirical law which used primary data and secondary data. The primary data directly got from the respondents, those are the students and the counselor teachers. The secondary data got from the books and literatures, policies, seminar result and any supported data. the result of the research shows that factors cause the inter school gang fight are some unimportant and trivial things such as so-closed school place, competition, missunderstanding, revenge, and economical problem. Alternate solution of inter school gang fight are teaching the students more religion, do family-improvement, teaching the students about the character education, teaching the students about behavior of respecting each other, do visit each-others, practice the law, make a peace agreement inter school gang fight